2005
DOI: 10.1002/jcop.20062
|View full text |Cite
|
Sign up to set email alerts
|

Children of mothers with histories of substance abuse, mental illness, and trauma

Abstract: Children exposed to parental substance abuse, mental illness, and violence face profound challenges, including increased risk for emotional and behavioral problems, substance abuse, and victimization. In this article, we describe the characteristics of a sample of children of women entering treatment. These children had been exposed to domestic violence, frequent child welfare involvement, and residential instability. Parental entry into treatment affords treatment providers an opportunity to intervene early w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 41 publications
1
43
0
3
Order By: Relevance
“…Children of mothers with a serious mental illness are at a heightened risk of developing psychiatric disorders (Lapalme et al 1997;Mowbray and Mowbray 2006;Rutter and Quinton 1984;Seeman 2004;VanDeMark et al 2005). For example, Pilowsky et al (2006) concluded that the current and lifetime prevalence of psychiatric diagnosis in children of mothers with depression was 34 and 45%, respectively.…”
Section: Impact Of Mental Health and Environmental Issues On Parentingmentioning
confidence: 97%
See 1 more Smart Citation
“…Children of mothers with a serious mental illness are at a heightened risk of developing psychiatric disorders (Lapalme et al 1997;Mowbray and Mowbray 2006;Rutter and Quinton 1984;Seeman 2004;VanDeMark et al 2005). For example, Pilowsky et al (2006) concluded that the current and lifetime prevalence of psychiatric diagnosis in children of mothers with depression was 34 and 45%, respectively.…”
Section: Impact Of Mental Health and Environmental Issues On Parentingmentioning
confidence: 97%
“…Risk of developing many forms of mental illness is inherited. However, risk may be increased by social and environmental factors such as poverty, social isolation, family discord and domestic violence, which in turn, may be caused or compounded by parental substance abuse and other co-morbidity (Lancaster 2004;Lapalme et al 1997;VanDeMark et al 2005;Velleman 2004). This research highlighting risk is balanced by other research revealing resilience.…”
Section: Impact Of Mental Health and Environmental Issues On Parentingmentioning
confidence: 99%
“…Discussing parenting and the wellbeing of their children with parents who enter substance abuse treatment can contribute to timely referral of CSAP to appropriate help. This emphasizes the need for a more family-oriented approach with special attention paid to children and parenting issues in adult facilities for mental and substance abuse treatment (Gruenert et al, 2006;VanDeMark et al, 2005. …”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported elevated rates of mental health problems in these children, such as the study by VanDeMark et al (2005), which assessed 253 children (5-10 years) of mothers who entered treatment for substance abuse, domestic violence, and trauma problems. Of these children, 40% showed signs of internalizing problem behavior and 37% showed signs of externalizing problem behavior.…”
mentioning
confidence: 99%
“…Les barrières liées aux problématiques de santé mentale sont à considérer de façon particulière étant donné qu'elles sont de plus en plus présentes en centre jeunesse et ce, tant chez les enfants que chez les parents (Centre jeunesse du Saguenay-Lac-Saint-Jean, partie les difficultés liées à l'implication parentale par la présence de problèmes psychiatriques, car on constate de plus en plus l'influence des symptômes de la maladie mentale des parents sur les enfants (Boily, Lew & Morissette 1998VanDeMark, Russell, O'Keefe, Finkelstein, Noether & Gampel, 2005). De son côté, Parmentier (1990) a souligné que la prise en charge d'une situation où la mère est atteinte d'une maladie mentale grave peut faire ressurgir, chez les intervenants, des sentiments violents et une augmentation de l'angoisse qui peuvent influencer négativement la participation des parents.…”
Section: Historiqueunclassified